Pornografi, Remaja, dan Pendidikan Seks Dalam Islam - Dawam, Ainurrafiq (Musawa Jurnal Studi Gender dan Islam, 2006)
Today the most popular infonnation for Indonesians is about pornography. In general, attitudes toward pornography can be classified into four major perspectives: conservative, feminist, postmodernist, and liberal. For adolescents pornography is a new world after they leave their childhood, and they should be protected from the hazard of pornography. They must be equipped with good knowledge and strong faith to Allah. One of the many ways of preventing teenagers from being negatively affected by pornography is education, especially providing sex education from an Islamic perspective. Historically there were subjects on sexuality in Islamic scholarship. This article aims at describing trends of adolescents' attitudes toward pornography, and proposes a concept of sex education in an Islam perspective in order to free them from negative impacts of pornography.